Enzymatic Characterization of SpPAL Genes in S. polyrhiza and Overexpression of the SpPAL3 - Xiaoxue Li; Yinxing Zhang; Chunfeng Zhu; Pufan Zheng; Cunkun Chen; Na Zhang; Haipeng Ji; Chenghu Dong; Jinze Yu; Jie Ren; Yerong Zhu; Yong Wang (Plants)
Phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) catalyzes the deamination of phenylalanine, which is the initial step in the biosynthesis of phenylpropanoids. It serves as a crucial enzyme that facilitates the transfer of carbon from primary to secondary metabolism in plants. Duckweed is regarded as a promising chassis plant in synthetic biology research and application, due to its being rich in secondary metabolites and other advantages. The genes encoding PAL in Spirodela polyrhiza (L.) Schleid, the giant duckweed, were investigated in this study. Three SpPAL genes (SpPAL1–SpPAL3) were identified and cloned. All of them were successfully expressed in E. coli, and their recombinant proteins all showed PAL activity. In addition, SpPAL1 and SpPAL2 proteins could also utilize tyrosine as substrate, although the activity was low. A qRT-PCR analysis demonstrated that the expression of SpPAL3 was most pronounced in young fronds. It was found that the expression of SpPAL1 and SpPAL3 was significantly induced by MeJA treatment. Overexpression of SpPAL3 in Lemna turionifera inhibited the growth of fronds and adventitious roots in the transgenic plants, indicating the importance of SpPAL3 in duckweed besides its involvement in the secondary metabolism.